MOTIVASI IBU HAMIL DALAM MELAKUKAN PEMERIKSAAN RUTIN ANTENATAL CARE (ANC) MENGGUNAKAN MOTIVATION FOR HEALTH BEHAVIOR SCALE (MHBS) - Rochmawati, Rochmawati; Damayanti, Rini (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2025)
Efforts to reduce maternal death rates rely on regular Antenatal Care (ANC) checks, but coverage is still not ideal, especially in places with restricted access. We want to learn more about pregnant women's motivations for getting annual cervical screenings (ANC) and how those motivations relate to sociodemographic variables and compliance rates in this research. The study used a cross-sectional design and a selective sample strategy to choose 128 pregnant women from Bogor Regency. The Motivation for Health Behavior Scale (MHBS), a reliable and effective tool for measuring motivation, was used to assess the following: autonomous motivation, regulated motivation, and amotivation. In terms of autonomous motivation, 54.7% of respondents were very motivated and 68.0% were very unmotivated, according to the results. A substantial association between education level and autonomous motivation was found by correlational analysis (r=0.624, p<0.01), and a high correlation between family support and autonomous motivation was also found (r=0.712, p<0.001). With 82.9% of respondents in this group achieving the suggested visit requirements, there was a significant association between high autonomous motivation and ANC compliance (χ²=18.762, p<0.001). Personalized intervention approaches based on sociodemographic characteristics and dominant motivation dimensions should ideally be the focus of strategies to improve ANC compliance. It is important to consider the involvement of family support systems as catalysts for preventive health behavior change.